2016
DOI: 10.1002/aenm.201502276
|View full text |Cite
|
Sign up to set email alerts
|

Is the Cu/Zn Disorder the Main Culprit for the Voltage Deficit in Kesterite Solar Cells?

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
245
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(260 citation statements)
references
References 123 publications
7
245
1
7
Order By: Relevance
“…Cu 2 ZnSnS 4 has a similar Urbach energy and has a V OC 0.5 V below its Shockley-Queisser limit value. [46,50] Band tails and sub-bandgap states present in the NiO x ( Figure S43, Supporting Information) and ZnO layers (measured previously, [45,51] and from Figure S42, Supporting Information) can also lead to V OC losses due to carrier thermalization or recombination from the band tails. [45,52] Further device modeling and temperature-dependent V OC measurements are required to quantify the magnitudes of these different effects.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Cu 2 ZnSnS 4 has a similar Urbach energy and has a V OC 0.5 V below its Shockley-Queisser limit value. [46,50] Band tails and sub-bandgap states present in the NiO x ( Figure S43, Supporting Information) and ZnO layers (measured previously, [45,51] and from Figure S42, Supporting Information) can also lead to V OC losses due to carrier thermalization or recombination from the band tails. [45,52] Further device modeling and temperature-dependent V OC measurements are required to quantify the magnitudes of these different effects.…”
mentioning
confidence: 69%
“…Disorder in the BiOI absorber could lead to V OC losses, for example due to potential fluctuations in the bandgap. [50] Using photothermal deflection spectroscopy, we measured the Urbach energy to be 70 meV for BiOI grown on quartz, and 90 meV for BiOI grown on NiO x on quartz ( Figure S43, Supporting Information). Cu 2 ZnSnS 4 has a similar Urbach energy and has a V OC 0.5 V below its Shockley-Queisser limit value.…”
mentioning
confidence: 99%
“…Bourdais & al. 40 have shown that CZTSSe samples can have a Cu/Zn disorder ranging from 20% to 100% at room temperature. They demonstrate as well that Cu/Zn disorder does not have an impact on solar cell efficiency in this range of values.…”
Section: Occurrence Quantification In Literaturementioning
confidence: 99%
“…It is worth noticing that both causes cannot be considered at the same level. While band tails (due to electrostatic potential fluctuations or bandgap fluctuations) are directly linked to structural defects in the material (presence of secondary phases in the bulk of the material 12 , Cu/Zn disorder 39 , locally inhomogeneous distribution of the anion 40 , high level of compensated defects 38 ), short minority carrier lifetime might be considered as a potential consequence of similar defects. Shockley-Read-Hall (SRH) recombination on point defects in the bulk of the absorber is generally said to be responsible for this short lifetime 42 but the influence of band tails, grain boundaries or even interfaces on lifetime is rarely discussed 13 .…”
Section: Mapping Of Fundamental Failures In Cd-free Kesterite Solar Cmentioning
confidence: 99%
“…[2] Alkali treatment of kesterite solar cells is one of the measures to reduce the high V OC -deficit and most of today's >10% efficiency kesterite devices utilize the beneficial effects of alkali elements on absorber layer morphology and optoelectronic properties. So far the most research attention has been paid to sodium, resulting in many thorough investigations which revealed grain size enhancement, passivation of grain boundaries, and an increase in net hole concentration as the major beneficial effects of sodium treatments.…”
mentioning
confidence: 99%